PENGARUH LITERASI KEUANGAN, GAYA HIDUP DAN UANG SAKU TERHADAP PERILAKU KEUANGAN MAHASISWA DI UNIVERSITAS MUHAMMADIYAH GRESIK - Faqqihatut Toyyibah; Anita Handayani (MANAJEMEN DEWANTARA, 2026)
This study aims to analyze the influence of financial literacy, lifestyle, and pocket money on the financial behavior of students in the Faculty of Economics and Business at Muhammadiyah University of Gresik. The research method used in this study was a deductive quantitative method with a sample of 169 students. The data analysis technique used was multiple linear regression analysis using the SPSS version 25 analysis tool. The results of the study showed that financial literacy had a significant positive effect on financial behavior, lifestyle had a positive but insignificant effect on financial behavior, and pocket money had a significant positive effect on financial behavior